Observations on the separation of iron ore in a prototype batch jig - Naude, N.; Lorenzen, L.; Kolesnikov, A.; Aldrich, Chris; Auret, L. (Elsevier, 2013)
The separation of iron ore in a prototype batch jig separator developed by Mintek in South Africa, referred to as the Mineral Density Separator (MDS), can separate ore samples into multiple bulk density fractions, provided that narrow feed size ranges are used. In this study, the performance of the equipment is considered by use of iron ore particles coloured according to density. This facilitated visualization of the density composition of the stratified ores. The highest density iron ore (>4000 kg/m3) could be separated efficiently from gangue material, but satisfactory stratification of lower density particles (<3600 kg/m3) could not be achieved.